Trends in cannabis use among immigrants in the United States, 2002–2017: Evidence from two national surveys. (December 2019) - Salas-Wright, Christopher P.; John, Rachel; Vaughn, Michael G.; Eschmann, Rob; Cohen, Mariana; AbiNader, Millan; Delva, Jorge
Abstract: Background and aims: Findings from recent studies suggest that, among the general population of adults, the prevalence of cannabis use has increased over the last decade in the United States (US). And yet, there is much we do not know regarding the trends in cannabis use among immigrants . We address this important shortcoming by examining data on immigrants vis-à-vis US-born individuals using two national surveys. Methods: We examine trend data from the National Epidemiologic Study on Alcohol and Related Conditions (NESARC, 2001–2013) and the National Survey on Drug Use and Health's Restricted Data Analysis System (NSDUH, 2002–2017). Main outcomes were past year cannabis use and cannabis use disorder with survey adjusted prevalence estimates generated for immigrants and US-born individuals. Results: In the NESARC, significant increases in the past year prevalence of cannabis use were observed both among US-born (2001–2002: 4.53%, 2012–2013: 10.74%) and immigrant participants (2001–2002: 1.67%, 2012–2013: 3.32%). We also found significant increases among immigrants arriving before age 12 and among immigrants from Latin America and Europe. In the NSDUH, we observed a significantly higher prevalence of cannabis use in 2016–2017 (6.3%) when compared to 2002–2003 (4.4%). Conclusions: Findings make clear that cannabis use among US-born individuals has consistently been higher than that of immigrants since the early 2000s. However, while rates of cannabis use have declined among US-born adolescents in recent years, the prevalence of cannabis use has remained stable among immigrant adolescents. At the same time, cannabis use increased two-fold among both US-born and immigrant adults.